IDENTIFIKASI TINGKAT KEKUMUHAN PERMUKIMAN DI SEKITAR MUARA KALI MARO KAWASAN KONDAP-CIKOMBONG, KELAPA LIMA, KOTA MERAUKE - Balagaize, Elisabeth Ella S.; Herlambang, Suryono; Suryadjaja, Regina (Jurusan Arsitektur dan Perencanaan, 2025)
Merauke City is the capital of South Papua Province which is located in the easternmost part of Indonesia and was inaugurated by President Joko Widodo in 2022. The area of ​​Merauke City is 45,013.35 km2 and borders directly with the State of Papua New Guinea. In line with its status as the Provincial Capital, the Merauke City Region is the center of economic activities, education, and more adequate living facilities, making it an attraction for people to migrate and can lead to an increase in population. One of the essences is that the need for organizational infrastructure and facilities continues to increase, resulting in a decrease in the carrying capacity of organizational environmental infrastructure and facilities in the Merauke City area. The plains of the city of Merauke are areas bordered by water areas in the form of swamps, the sea, and the Maro River Estuary, which are the icons of Merauke City. The aim of this research is to determine the level of slums and directions for structuring settlements around Muara Kali Maro in the Kondap - Cikombong area, Kelapa Lima Village, Merauke City. There are four analyses used in this research, namely Policy Analysis, River Border Line Analysis, Land Status Analysis, and Slum Level Analysis with Scoring calculations to determine the level of slums and recommend structuring directions at the location of the study object. Based on the results of the analysis of the location of the Kondap-Cikombong slum organization in Merauke City, which is located on a land area of ​​9.12 hectares, it is in the level of heavy slum with a score of 73, so there is a need for improvements and arrangements in housing conditions and infrastructure as an effort to increase the level of quality of life of the community in inside it. Keywords: Area; City; Merauke; Settlement; Slum; Structuring Abstrak Kota Merauke merupakan Ibu Kota Provinsi Papua Selatan yang terletak di bagian Paling Timur Indonesia dan baru saja diresmikan oleh Presiden Joko Widodo pada tahun 2022 silam. Luas Wilayah Kota Merauke adalah 45.013,35 km2 serta berbatasan langsung dengan Negara Papua New Guinea. Sejalan dengan statusnya sebagai Ibu Kota Provinsi Kawasan Kota Merauke merupakan pusat dari kegiatan ekonomi, pendidikan, serta fasilitas kehidupan yang lebih memadai, sehingga menjadi daya tarik bagi masyarakat untuk melakukan migrasi dan dapat menyebabkan peningkatan jumlah penduduk. Salah satu implikasinya adalah kebutuhan prasarana dan sarana permukiman terus meningkat, sehingga mengakibatkan penurunan daya dukung prasarana dan sarana lingkungan permukiman pada daerah Kota Merauke. Dataran kota merauke merupakan daerah yang dibatasi dengan daerah perairan berupa rawa, Laut dan Muara Kali Maro yang menjadi iconic Kota Merauke. Tujuan dari penelitian ini untuk mengetahui tingkat kekumuhan dan arahan penataan Permukiman di Sekitar Muara Kali Maro, Kawasan Kondap - Cikombong, Kelurahan Kelapa Lima, Kota Merauke. Terdapat empat analisis yang digunakan pada penelitian ini, yaitu Analisis Kebijakan, Analisis Garis Sempadan Sungai, Analisis Status Lahan dan Analisis Tingkat Kekumuhan dengan menghitung Scoring untuk mengetahui tingkat kekumuhan dan merekomendasikan arahan penataan pada lokasi objek studi. Berdasarkan hasil analisis lokasi permukiman kumuh Kondap-Cikombong kota Merauke yang berdiri di tanah seluas 9,12 ha ini ada dalam tingkat kekumuhan berat dengan skor 73, sehingga perlu adanya perbaikan dan penataan pada kondisi perumahan dan infrastruktur sebagai upaya untuk meningkatkan tingkat kualitas hidup masyarakat di dalamnya.